Treatment decision-making in acute myeloid leukemia: a qualitative study of older adults and community oncologists. Issue 2 (28th January 2021) - Loh, Kah Poh; Abdallah, Maya; Kadambi, Sindhuja; Wells, Megan; Kumar, Anita J.; Mendler, Jason H.; Liesveld, Jane L.; Wittink, Marsha; O'Dwyer, Kristen; Becker, Michael W.; McHugh, Colin; Stock, Wendy; et al.
Abstract: Little is known about the characteristics of patients, physicians, and organizations that influence treatment decisions in older patients with AML. We conducted qualitative interviews with community oncologists and older patients with AML to elicit factors that influence their treatment decision-making. Recruitment was done via purposive sampling and continued until theoretical saturation was reached, resulting in the inclusion of 15 patients and 15 oncologists. Participants' responses were analyzed using directed content analysis. Oncologists and patients considered comorbidities, functional status, emotional health, cognition, and social factors when deciding treatment; most oncologists evaluated these using clinical gestalt. Sixty-seven percent of patients perceived that treatment was their only option and that they had not been offered a choice. In conclusion, treatment decision-making is complex and influenced by patient-related factors. These factors can be assessed as part of a geriatric assessment which can help oncologists better determine fitness and guide treatment decision-making.